Pengaruh Depresiasi Terhadap Nilai Wajar Aset Dan Implikasinya Terhadap Penghapusan Barang Milik Negara (BMN) - Putra, Sukeng Ngesti Rahtama; Pratiwi, Ananta Dian (Jurnal Ilmiah Raflesia Akuntansi, 2024)
The purpose of this paper is to determine the effect of depreciation value calculations on the fair value of a State Property (BMN) asset and the impacts caused when the asset is written off either through pure write-off and transfer. Adjusting the applicable regulations regarding the mechanism for calculating the depreciation value of an asset. What is the procedure for recording the fair value of assets and writing off State Property (BMN) in accordance with applicable regulations. Disclosure and recording in the financial statements of a government institution must be based on correct calculations and refer to applicable laws and regulations. As a reference for the office to carry out the process of managing State Property (BMN) asset units so that they are appropriate and do not experience fatal damage so that the useful life of the goods can be as long as possible even though the regulations have an age limit. To gain a deeper understanding of the topic being studied, the researcher used a qualitative descriptive research method. Using data obtained from the State Asset Management Information System (SIMAN) application at the Banggai District Attorney's Office Branch in Bunta and direct observation of the asset objects to be studied.